Pengukuran Tingkat Eko-efisiensi Menggunakan Life Cycle Assessment untuk Menciptakan Sustainable Production di Usaha Kecil Menengah Batik - Diana Puspita Sari; Sri Hartini; Dyah Ika Rinawati; Tri Setyo Wicaksono (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
Pekalongan is one of the batik cities in Central Java, many batik SMEs thrive in Pekalongan. Batik SMEs indicated a cause of environmental pollution that occurred in the city of Pekalongan. Pollution caused by the use of chemicals in the dyeing process. This study aims to measure the eco-costs and eco-efficiency rate of batik products, as well as looking for suggestions on improving eco-efficiency. Eco-efficiency rate is measured by using LCA (Life Cycle Assess-ment) doped with SimaPro software. This method is used to evaluate the environmental impacts arising from the use of the constituent materials. The results of the data processing show that the value of eco-costs for chemical dye batik is Rp 188,028.32, with eco-efficiency rate is 68.74%. Batik industries are not sustainable and affordable. Economizing of the resourcing and applying cleaner production can be accomplished to enhance the eco-efficiency rate. Cleaner production can be achieved using natural dyes and implement End of Life strategies.